2014
DOI: 10.1007/s00213-014-3624-0
|View full text |Cite
|
Sign up to set email alerts
|

A study of antioxidant activity in patients with schizophrenia taking atypical antipsychotics

Abstract: IntroductionAtypical antipsychotics have significantly improved the quality of life for schizophrenic patients. Despite their beneficial effects, these antipsychotics induce weight gain, diabetes, and dyslipidemia. The aims of this study were to investigate the antioxidative activity of paraoxonase and assess lipid profile as a cardiovascular risk factor in patients with schizophrenia under long-term clozapine or risperidone treatment.MethodsThe study included 66 patients with schizophrenia under clozapine or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
54
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(55 citation statements)
references
References 42 publications
1
54
0
Order By: Relevance
“…Paraoxonase 1 (PON1) is an antioxidant enzyme synthesized by the liver and bound to highdensity lipoprotein (HDL), protecting HDL particles against OS damage (Precourt et al, 2011). In schizophrenia, there are only few data on PON1, reporting both normal and reduced activity (Gilca et al, 2014;Mabrouk et al, 2014;Unsal et al, 2013). No studies, however, examined PON1 activity in drug naïve individuals separately.…”
Section: Introductionmentioning
confidence: 98%
“…Paraoxonase 1 (PON1) is an antioxidant enzyme synthesized by the liver and bound to highdensity lipoprotein (HDL), protecting HDL particles against OS damage (Precourt et al, 2011). In schizophrenia, there are only few data on PON1, reporting both normal and reduced activity (Gilca et al, 2014;Mabrouk et al, 2014;Unsal et al, 2013). No studies, however, examined PON1 activity in drug naïve individuals separately.…”
Section: Introductionmentioning
confidence: 98%
“…Rozenberg et al reported that PON1 induces a decrease in the accumulation of cholesterol at the level of macrophages by the inhibition of its biosynthesis [27]. Rosenblat et al showed that HDL-induced cholesterol efflux from transgenic mice over-expressing PON1 was greater than that provided by HDL from wild-type mice or invalidated mice for the gene of the PON1 [28].…”
Section: Discussionmentioning
confidence: 99%
“…Atypical antipsychotics induce weight gain, diabetes, and dyslipidaemia [57]. The pts with schizophrenia might be at increased risk for metabolic and CVD [57].…”
Section: Heart Muscle Diseasementioning
confidence: 99%
“…The pts with schizophrenia might be at increased risk for metabolic and CVD [57]. By available data, clozapine is an atypical antipsychotic medication which remains the gold standard in treatment of resistant psychosis [58].…”
Section: Heart Muscle Diseasementioning
confidence: 99%